Stop wasting food and money by safely storing leftovers - Kolasa, Kathryn M; Anderson, Haley G (My University, 2022)
This is a weekly Q and A newspaper column under the byline of Dr. Kathy Kolasa. Today's column is about how to make good use of leftovers without getting food poisoning.
Medical and dietetic students often co-author a column for the Daily Reflector under Dr. Kolasa's byline. The students research the topic a reader or patient has asked. Dr. Kolasa reviews their draft for technical accuracy, patient-friendly language, people-first language. She fact checks the study or other evidence-based reference the student provides. If a physician review is appropriate, Dr. Kolasa requests a colleague from ECU physicians to review the article. The final draft is submitted to the Reflector with the editor having the final say. The headline is written by the Reflector headline writer. The food and nutrition column has run weekly since 1987. Starting in 2020, in addition to the Daily Reflector, the article is published in daily and weekly papers owned by the Adams Publishing Group East (https://adamspg.com)
Keywords: medicine, nutrition, food waste, leftovers, foodborne illness